2001
DOI: 10.1093/humrep/16.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in infants born after IVF: a population-based study

Abstract: The presence of congenital malformations in infants born after IVF was studied from a register consisting of practically all infants born in Sweden after IVF, 1982--1997 (n = 9111). A further 64 infants were studied using only medical records. It is a nation-wide study and has a population-based control group (n = 1,690,577) and relevant potential confounders have been taken into account. There was an excess of congenital malformations registered in the Medical Birth Registry (n = 516, odds ratio = 1.47) but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
184
3
15

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(218 citation statements)
references
References 17 publications
15
184
3
15
Order By: Relevance
“…The apparent lack of risk of SSR alteration under IUI may reflect a genuine lack of effect of it could be due to the relatively small sample size recorded for IUI. Overall, these results are qualitatively consistent with previous observations of lower SSR after ICSI and higher SSR following IVF (8,(27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
“…The apparent lack of risk of SSR alteration under IUI may reflect a genuine lack of effect of it could be due to the relatively small sample size recorded for IUI. Overall, these results are qualitatively consistent with previous observations of lower SSR after ICSI and higher SSR following IVF (8,(27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
“…The details of the meta-analysis-including the literature search, the study selection and the data extraction processes-are described there. We found 19 studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for inclusion in the meta-analysis and found that ART increased the risk of MM with an odds ratio of 1.29 (95% CI 1.01-1.67). Our major conclusion was that the risk we found may be inflated by the fact that none of the studies used the most appropriate control group, namely subfertile couples conceiving spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The range varies from no difference compared to a naturally conceived population to a doubling of the congenital malformation rate (Table 2). 16,17 The Norwegian Health Technology Assessment systematic review 18 of offspring of ICSI pregnancies summarises that there is a small increased risk of Where no detail of case matching is given none is reported. CA ϭ child's age I ϭ previous subfertility M ϭ multiplicity MA ϭ maternal age MB ϭ multiple births ME ϭ maternal education OR ϭ odds ratio (95% CI) P ϭ parity Qs ϭ quads R ϭ race RB ϭ region of birth RR ϭ relative risk (95% CI) S ϭ child's sex SC ϭ social class Sgs ϭ singletons Trs ϭ triplets Tws ϭ twins YOB ϭ year of birth major birth defects (RR 1.13, 95% CI 1.00-1.29, P = 0.06) in children born using ICSI in comparison with naturally conceived controls, although clearly the confidence interval for this meta-analysis does reach 1.0.…”
Section: Congenital Malformationsmentioning
confidence: 99%